Behavioral implementation without unanimity - Ville Korpela; Michele Lombardi; Julius Zachariassen (Aboa Centre for Economics (ACE), 2024)
Behavioral implementation studies implementation when agents' choices need not be rational. All existing papers of this literature, however, fail to handle a large class of choice behaviors because they rely on a well-known condition called Unanimity. This condition says, roughly speaking, that if all agents would select the same outcome form the set of all feasible outcomes, then this outcome should be deemed socially optimal. While Unanimity is both sensible as a property of a goal and necessary for implementation under rational behavior, with non-rational behavior it is neither. In this paper we investigate behavioral implementation under complete information without assuming Unanimity. Moreover, we give a full characterization of behaviorally implementable SCRs when the designer can use individually based rights structure.
Keywords: C72; D11; D71; D82; 330; Behavioral economics; Implementation theory; Rights structure; Unanimity